The relations of daily task accomplishment satisfaction with changes in affect: A multilevel study in nurses. - Gabriel, Allison S.; Diefendorff, James M.; Erickson, Rebecca J. (Journal of Applied Psychology, 2011)
Focusing on a sample of nurses, this investigation examined the relationships of daily task accomplishment satisfaction (for direct and indirect care tasks) with changes in positive and negative affect from preshift to postshift. Not accomplishing tasks to one's satisfaction was conceptualized as a daily workplace stressor that should increase daily negative affect and decrease daily positive affect from preshift to postshift. Further, because of the greater centrality of direct care nursing tasks to nursing work role identities (relative to indirect care tasks), we expected that task accomplishment satisfaction (or lack thereof) for these tasks would have stronger effects on changes in affect than would task accomplishment satisfaction for indirect care tasks. We also examined 2 person-level resources, collegial nurse-physician relations and psychological resilience, as moderators of the relationships among these daily variables, with the expectation that these resources would buffer the harmful effects of low task accomplishment satisfaction on nurse affect. Results supported almost all of the proposed effects, though the cross-level interactions were observed only for the effects of indirect care task accomplishment satisfaction on affect and not for direct care task accomplishment satisfaction on affect.